2018
DOI: 10.1007/s10637-018-0650-5
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 dose-escalation study of momelotinib, a Janus kinase 1/2 inhibitor, combined with gemcitabine and nab-paclitaxel in patients with previously untreated metastatic pancreatic ductal adenocarcinoma

Abstract: Purpose Preclinical evidence suggests the importance of Janus activating kinase (JAK) and TANK-binding kinase 1 (TBK1) in pancreatic ductal adenocarcinoma (PDAC). We evaluated the safety and efficacy of momelotinib (MMB), a JAK1/2 inhibitor with additional activity against TBK1, plus albumin-bound paclitaxel + gemcitabine (nab-P + G), in patients with previously untreated metastatic PDAC. Experimental Design Patients were enrolled into five cohorts of increasing doses of MMB between 100 and 200 mg administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 20 publications
0
33
1
Order By: Relevance
“…Over the course of an 18 h treatment, PNPLA3 mRNA was reduced up to 80% at 10 μM, without affecting cell viability ( Figure 1 a). Of note, 10 μM is roughly five-fold lower than the peak plasma concentration achieved with a single 150 mg oral dose of momelotinib in a dose escalation study in metastatic cancer patients [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Over the course of an 18 h treatment, PNPLA3 mRNA was reduced up to 80% at 10 μM, without affecting cell viability ( Figure 1 a). Of note, 10 μM is roughly five-fold lower than the peak plasma concentration achieved with a single 150 mg oral dose of momelotinib in a dose escalation study in metastatic cancer patients [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Its impact in solid tumors is under active clinical investigation. In a Phase I doseescalation study in patients with untreated metastatic pancreatic cancer, momelotinib in combination with gemcitabine and nab-paclitaxel was well-tolerated; however, limited efficacy and no apparent association between efficacy and increasing dose led to the termination of this trial prior to the initiation of planned Phase III studies (NCT02101021) [122] . A Phase Ib study of momelotinib combined with trametinib in KRAS-mutated NSCLC showed no improvement in response compared with historic data with trametinib monotherapy (NCT02258607) [123] .…”
Section: Momelotinibmentioning
confidence: 99%
“…Application of another JAK1/2 inhibitor, momelotinib, in combination with gemcitabine and nab-paclitaxel for patients with previously untreated metastatic pancreatic cancer demonstrated that the combination was well tolerated but exhibited no clinical benefit compared with gemcitabine/nab-paclitaxel dual treatment [264]. Ongoing studies trialling the combination of STAT3 inhibitor napabucasin with gemcitabine/nab-paclitaxel in patients with metastatic pancreatic cancer demonstrated that the treatment is well tolerated, though conclusive results regarding efficacy are pending [265,266].…”
Section: Clinical Trials Targeting Jak1/2 or Stat3 Are Ongoingmentioning
confidence: 99%